A Review on the Ingredients of Triphala (Harro, Barro and Amala) - Ghimire, Alizza; Bhattarai, Pratima; Adhikari, Promish (Kalika Journal of Multidisciplinary Studies, 2023)
Triphala is a poly-herbal formula made up of three equal proportions of herbal fruits, Harro, Barro, and Amala, found in tropical and sub-tropical regions of Asia. This study aimed to review the phytochemicals, potential uses, and constituents of Triphala using PRISMA standards. Data was collected from well-known bibliometric information sources. All the obtained information was analysed systematically and represented in a tabular and descriptive form. The result shows that the main chemical constituents of Triphala include Vitamin C, carotene, nicotinic acid, riboflavin, tannins, tannins, anthraquinones, polyphenolic compounds, and gallic acid, tannic acid, and glycosides. Triphala is crucial for balancing and rejuvenating three constitutional elements that govern human life. Its biological activities include anti-microbial, anti-oxidant, anti-arthritic, anti-stress, antipyretic, analgesic, anti-diarrheal, gastrointestinal protective, hepatoprotective, anti-hyperglycemic, cardioprotective, hypolipidemic, wound healing, antineoplastic, radio-protective, chemoprotective, chemopreventive, mutagenesis and DNA damage prevention, anti-cataractogenesis, anti-lipid peroxidative, free radical scavenging, and anti-inflammatory. Triphala is a novel drug with numerous therapeutic potentials, effective in maintaining health, preventing diseases, and treating various ailments. This herbal aptitude of Triphala promotes the development of a medical system with minimal side effects. Therefore, it is necessary to ensure that the local population is provided with accurate information regarding triphala.